SUVN‐D4010: A serotonin‐4 receptor partial agonist for the treatment of cognitive disorders. (1st February 2022) - Medapati, Rajesh Babu; Ganuga, Narender; Mekala, Venkat Reddy; Bhyrapuneni, Gopinadh; Thentu, Jagadeesh Babu; Daripelli, Saivishal; Gagginapalli, Shankar Reddy; Bogaraju, Narsimha; Rasheed, Mohammed Abdul; Nirogi, Ramakrishna
Abstract: Background: Memory impairments are clinical symptoms of a wide range of neurodegenerative diseases, and natural physiological process such as ageing. SUVN‐D4010 is an investigational clinical candidate which acts by modulating 5‐HT4 receptors. Experimental evidences from animals and humans suggest that 5‐HT4 receptor activation holds promise for the treatment of cognitive impairment. Additionally, activation of 5‐HT4 receptor also modulates mood. The present investigation is to characterize SUVN‐D4010 and evaluate its drug‐like properties. Method: SUVN‐D4010 has been studied for its affinity and functional activity at 5‐HT4 receptor using in vitro methods. ADME properties were evaluated using in vitro and in vivo methods. SUVN‐D4010 was studied for its effects on learning and memory using social and object recognition tasks. The effects on the neurotransmitters were monitored using the brain microdialysis technique in rats. The effects on the beta amyloid processing were studied using in vitro and in vivo systems. The safety and tolerability was evaluated in both animals and humans. Result: SUVN‐D4010 showed potent affinity towards 5‐HT4 receptor when tested using radioligand binding and cell based reporter gene assay. SUVN‐D4010 has minimal binding over 70 target sites (at 1 µM, Caliper) including GPCRs, transporters, ion channels, peptides, steroids, second messengers, growth factors and prostaglandins. SUVN‐D4010 is orally bioavailable with good brain penetration and CSF concentrations. The likelihood of drug‐drug interaction of SUVN‐D4010 as an inhibitor/ inducer is remote. No unique metabolites were identified in non‐clinical and clinical samples. SUVN‐D4010 showed procognitve effects at doses ranging from 0.3 to 3 mg/kg, p . o . SUVN‐D4010 significantly increased extracellular acetylcholine levels as a standalone, or treatment adjunct to donepezil. SUVN‐D4010 promoted non‐amyloidogenic APPα processing and reduced toxic Aβ load. SUVN‐D4010 was found to be safe and well tolerated in healthy human volunteers. Conclusion: SUVN‐D4010 is a potent, selective, orally bioavailable and brain penetrant 5‐HT4 receptor partial agonist with potential utility in treatment of cognitive disorders.